Pengaruh Pengelompokkan Kelas Riset Robotika Terhadap Prestasi Belajar Pendidikan Pancasila - Lestari, Dwi Indah; Kurnia, Heri; Paiman, Paiman (Jurnal Kewarganegaraan, 2024)
AbstractThe effect of grouping robotics research classes on learning achievement in Pancasila education has become an interesting research focus in the context of modern education. This article discusses the background to the integration of technology in education, the relevance of combining robotics and Pancasila Education, and the importance of understanding the relationship between the two. This research method involves descriptive statistical analysis and simple linear regression with a population of 382 students and a sample of 192 students. Data was obtained from questionnaires and documentation through report cards from robotics research classes at MTs Negeri 1 Yogyakarta. The results of the analysis show that the instruments used are valid and reliable, and there is a significant relationship between the robotics research class grouping and Pancasila Education learning achievement. The results of simple linear regression show that around 73.1% is significant and 26.9% is influenced by other variables not included in this research. In conclusion, there is a significant influence of the robot research class grouping on Pancasila Education learning achievement. These findings show the potential for using technology such as robotics to improve learning of traditional subjects such as Pancasila Education at MTs Negeri 1 Yogyakarta.-------------------------AbstrakPengaruh pengelompokkan kelas riset robotika terhadap prestasi belajar Pendidikan Pancasila telah menjadi fokus penelitian yang menarik dalam konteks pendidikan modern. Artikel ini membahas latar belakang integrasi teknologi dalam pendidikan, relevansi penggabungan antara robotika dan Pendidikan Pancasila, serta pentingnya memahami hubungan antara keduanya. Metode penelitian ini melibatkan analisis deskriptif statistik dan regresi linier sederhana dengan populasi 382 siswa dan sampel 192 siswa. Data diperoleh dari kuesioner dan dokumentasi melalui nilai rapor kelas riset robotika di MTs Negeri 1 Yogyakarta. Hasil analisis menunjukkan bahwa instrumen yang digunakan valid dan reliabel, serta terdapat hubungan yang signifikan antara pengelompokkan kelas riset robotika dan prestasi belajar Pendidikan Pancasila. Hasil regresi linier sederhana menunjukkan bahwa sekitar 73.1% signifikan dan 26,9% dipengaruhi oleh variabel lain yang tidak dimasukkan kedalam penelitian ini. Kesimpulannya, terdapat pengaruh yang signifikan pengelompokkan kelas riset robotika terhadap prestasi belajar Pendidikan Pancasila. Temuan ini menunjukkan potensi penggunaan teknologi seperti robotika dalam meningkatkan pembelajaran mata pelajaran tradisional seperti Pendidikan Pancasila di MTs Negeri 1 Yogyakarta.